5-Aminosalicylic acid inhibits inflammatory responses by suppressing JNK and p38 activity in murine macrophages. (2nd January 2017) - Qu, Tingli; Wang, Erbing; Jin, Baofen; Li, Weiping; Liu, Ruiling; Zhao, Zheng-bao
Abstract: Context: 5-Aminosalicylic acid (5-ASA), as an anti-inflammatory drug, has been extensively used for the treatment of mild to moderate active ulcerative colitis (UC), but the possible mechanisms of action remain unclear. Objective: To investigate the effects of 5-ASA on the production of inflammatory mediators by murine macrophages stimulated with lipopolysaccharide (LPS), and determine the underlying pharmacological mechanism of action. Materials and methods: The levels of nitric oxide (NO) and interleukin-6 (IL-6) were measured by Varioskan Flash and IL-6 Enzyme-Linked Immunosorbent Assay sets. Real time quantitative polymerase chain reaction was used to determine the level of induced nitric oxide synthase (iNOS). The effects of 5-ASA on iNOS, the c-Jun N-terminal kinases (JNKs), p38 and nuclear factor (NF)-κB signaling pathways were examined using western blotting. Results: 5-ASA suppressed the production of NO and IL-6, and also decreased the expression of iNOS in LPS-induced RAW264.7 cells. 5-ASA inhibited the phosphorylation of JNKs and p38, but did not block NF-κB activation at all doses tested. Discussion and conclusion: The results indicated that the anti-inflammatory effect of 5-ASA was mainly regulated by the inhibition of the JNKs, p38 pathways rather than NF-κB pathway. Further research is required to clarify the detailed mechanism of the action.